Rule-Based System of Ammonia Gas Detection in Tofu Industry Based on Internet of Things and Cloud - Muhammad Shodiq; Dianda Aryntya Firia Ferlania (Universitas Panca Marga, 2025)
Industry of tofu is one of the driving forces of the economy but also has a negative impact because the waste produced can pollute the environment if not handled properly. Tofu industry waste is usually in the form of liquid waste containing several gases that are harmful to human health such as ammonia. Ammonia is a pollutant gas that causes health problems such as respiratory disorders to death. Therefore, a system is needed that is able to detect ammonia levels in tofu industry liquid waste. The purpose of this study is to develop a system that can monitor and provide real-time hazard notifications if ammonia levels are at a safe threshold. This study uses a rule-based system method for grouping ammonia level data, the Internet of Things (IoT) for real-time data collection devices, and the cloud to store data generated from IoT devices. The results of the study showed that ammonia levels were <200 ppm so that they were included in the alert category because the effects caused could cause irritation to the eyes, nose and throat.